2008
DOI: 10.1080/10286600701838667
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks based concrete airfield pavement layer moduli backcalculation

Abstract: The Heavy Weight Deflectometer (HWD) is a Non-Destructive Test (NDT) equipment used to assess the structural condition of airfield pavement systems. This paper presents an Artificial Neural Networks (ANN) based approach for non-destructively estimating the stiffness properties of rigid airfield pavements subjected to full-scale dynamic traffic testing using simulated new generation aircraft gears. HWD tests were routinely conducted on three Portland Cement Concrete (PCC) test items at the Federal Aviation Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…There is a very good agreement between the two, especially at lower k values. The NN-SCE NN predictions were also in agreement with the NN based backcalculation results reported by Ceylan et al (2008). …”
Section: Prediction Performance Of Nn-sce Backcalculation Approachsupporting
confidence: 80%
See 1 more Smart Citation
“…There is a very good agreement between the two, especially at lower k values. The NN-SCE NN predictions were also in agreement with the NN based backcalculation results reported by Ceylan et al (2008). …”
Section: Prediction Performance Of Nn-sce Backcalculation Approachsupporting
confidence: 80%
“…during trafficking further complicated the backcalculation analysis. Ceylan et al (2008) encountered similar difficulties when trying to backcalculate E values of NAPTF CC1 rigid pavement test items using NN-based inverse models.…”
Section: Lane 3: 4-wheel Trafficmentioning
confidence: 99%
“…Past studies revealed that there have been several successful studies that incorporated NNs to predict the pavement structural parameters such as pavement moduli, pavement layer thickness, etc. using falling weight deflectometer (FWD) deflection data (Meier & Rix, ; Williams & Gucunski, ; Meier et al ., ; Gucunski et al ., ; Kim & Kim ; Lee et al ., ; Saltan & Terzi, ; Ceylan et al ., ). The researchers concluded NNs to be more efficient and a better technique compared to conventional and traditional tools in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…From the laboratory test data for bituminous materials, NN was used to predict dynamic modulus of hot mix asphalt (Ceylan et al, 2008) and fatigue life (Huang et al, 2007). Xiao & Amirkhanian (2009b) involved NN to predict stiffness behaviour of rubberized asphalt concrete mixtures with reclaimed asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs' use has increased tremendously in solving complex civil engineering problems in 106 the last three decades (Ceylan et al 2014 First, the TSD deflection velocity 142 measurements were used to calculate the deflection basins through numerical integration. 143…”
Section: Artificial Neural Network (Ann) 101mentioning
confidence: 99%